1997
DOI: 10.1073/pnas.94.26.14456
|View full text |Cite
|
Sign up to set email alerts
|

d - myo -Inositol 1,4,5,6-tetrakisphosphate produced in human intestinal epithelial cells in response to Salmonella invasion inhibits phosphoinositide 3-kinase signaling pathways

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
1
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 30 publications
7
84
1
5
Order By: Relevance
“…Our previous studies have shown that SopB is an inositol phosphate phosphatase (14), and the recombinant protein assayed in vitro hydrolyzes a wide range of inositol phosphates and phospholipids (not including InsP 6 ). However, when a virulent strain of S. dublin is added to HeLa cells, it appears that Ins-1,3,4,5,6-P 5 is the major, if not only, phosphatase substrate with cellular levels of Ins-1,4,5,6-P 4 rising 14-fold in 30 min (14,15). Thus, other bacterial proteins besides SopB may be affecting intracellular inositol metabolites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have shown that SopB is an inositol phosphate phosphatase (14), and the recombinant protein assayed in vitro hydrolyzes a wide range of inositol phosphates and phospholipids (not including InsP 6 ). However, when a virulent strain of S. dublin is added to HeLa cells, it appears that Ins-1,3,4,5,6-P 5 is the major, if not only, phosphatase substrate with cellular levels of Ins-1,4,5,6-P 4 rising 14-fold in 30 min (14,15). Thus, other bacterial proteins besides SopB may be affecting intracellular inositol metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, when S. dublin was added to HeLa cells there was a rapid (1 h) increase in the levels of inositol 1,4,5,6-tetrakisphosphate (Ins-1,4,5,6-P 4 ) without significant changes in other inositol phosphates or phospholipids (14,15). This finding was significant because Ins-1,4,5,6-P 4 has been shown to antagonize the phosphatidylinositol 3,4,5-trisphosphate-mediated closing of cellular chloride channels (15). Thus, we speculated that SopB may enhance chloride and water secretion, thereby inducing diarrhea during infection.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The yeast homolog of IMPK -the kinase Arg82 -has been shown to be involved in transcriptional regulation suggesting a functional role of Ins(1,3,4,5,6)P 4 in regulation of gene expression. Furthermore, Ins(1,3,4,5,6)P 4 is elevated during Salmonella enterica infection [65]. In 2012, Watson et al [66] published the crystal structure of histone deacetylase 3 (HDAC3) in complex with the transcriptional co-repressor silencing mediator of retinoid and thyroid hormone receptors (SMRT).…”
Section: Inositol Tetraphosphatementioning
confidence: 99%
“…In fact, in addition to being preferred sites of infection in the natural hosts by the respective Salmonella host-restricted serotypes [215,216] (S. Uzzau and colleagues, unpublished results), they all represent primary lymphoid organs for the B-cell repertoire of that particular animal species. It is tempting to speculate, therefore, that a convergence exists between the evolution of S. enterica subspecies I strains able to colonize internal organs of warm blood animals, and the acquisition by these hosts of primary lymphoid tissues for B-cell maturation that are more sophisticated than those of the S. bongori and S. enterica subspecies II, IIIa, IIIb, IV, VI, and VII natural hosts, i.e.…”
Section: Extraintestinal Infection : Interaction With the Reticulo-enmentioning
confidence: 99%